2022
DOI: 10.2807/1560-7917.es.2022.27.7.2200060
|View full text |Cite
|
Sign up to set email alerts
|

Risk reduction of severe outcomes in vaccinated COVID-19 cases: an analysis of surveillance data from Estonia, Ireland, Luxembourg and Slovakia, January to November 2021

Abstract: Despite high COVID-19 vaccine coverage in the EU/EEA, there are increasing reports of SARS-CoV-2 infections and hospitalisations in vaccinated individuals. Using surveillance data from Estonia, Ireland, Luxembourg and Slovakia (January–November 2021), we estimated risk reduction of severe outcomes in vaccinated cases. Increasing age remains the most important driver of severity, and vaccination significantly reduces risk in all ages for hospitalisation (adjusted relative risk (aRR): 0.32; 95% confidence interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…Our results are largely in agreement with the findings of Moghadas et al, who found a similar significant reduction of adverse outcomes in vaccinated individuals compared to non-vaccinated individuals in the USA [ 18 ]. Similarly, Marrone et al found a reduced risk of severe cases in vaccinated compared to non-vaccinated individuals in some European countries, confirming old age as one of the main risk factors [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 92%
“…Our results are largely in agreement with the findings of Moghadas et al, who found a similar significant reduction of adverse outcomes in vaccinated individuals compared to non-vaccinated individuals in the USA [ 18 ]. Similarly, Marrone et al found a reduced risk of severe cases in vaccinated compared to non-vaccinated individuals in some European countries, confirming old age as one of the main risk factors [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 92%
“…This study has some limitations. Our results are not estimates of the vaccine effectiveness in preventing hospitalisations and severe disease in the population but among COVID-19 cases, and the vaccine effect in preventing SARS-CoV-2 infections was not considered [ 28 ]. Vaccination coverage varied greatly with age, comorbidity and month, but analyses were adjusted for these variables.…”
Section: Discussionmentioning
confidence: 99%
“…Risk reduction of severe disease a of full vaccination with booster dose vs full vaccination 6 months or more before positive test in COVID-19 cases by age, sex and underlying conditions, Navarre, Spain, 3 January-20 March 2022 (n =28,867) …”
mentioning
confidence: 99%
“…Such VOCs possess many amino acid substitutions in the spike (S) protein of SARS-CoV-2 that reduce the potency of the neutralizing antibodies that are induced by vaccination and SARS-CoV-2 infection. 5 , 6 Although the vaccines reduce the severity of COVID-19, 7 novel VOCs that escape from the neutralizing antibodies induced by vaccination and infection may continue to emerge.…”
Section: Introductionmentioning
confidence: 99%